Factors associated to knowledge and opinion of gynecologists and obstetricians about the Brazilian legislation on abortion - Anibal Faúndes; Rozana Martins Simoneti; Graciana Alves Duarte; Jorge Andalaft-Neto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2007)
INTRODUCTION: Unsafe abortion accounts for about 12% of maternal deaths in Brazil, although many of these women could meet the requirements for legal abortion in this country. Physicians' inappropriate knowledge of the law may be playing a role in this situation. OBJECTIVE: To evaluate which factors are associated with the level of information and the opinion of the Brazilian gynecologists-obstetricians concerning abortion laws. METHODS: Questionnaires (14.320) were sent to all physicians affiliated to the Brazilian Federation of Gynecology and Obstetrics Associations (FEBRASGO), and 30.2% were returned completed. RESULTS: Most of respondents showed a good knowledge of the situations in which abortion is allowed but not about the documents required to carry out a legal abortion. However, most of them knew about the need for a judicial order in case of abortion of malformed fetus. Knowledge was associated with age, number of children and years of practice. DISCUSSION AND CONCLUSIONS: Poor knowledge on the requirements to carry out an abortion within the law may be a main factor responsible for the lack of access to legal abortion in Brazil. INTRODUÇÃO: Estima-se que 12% dos casos de mortalidade materna no Brasil sejam conseqüência de aborto clandestino. Muitas dessas mulheres cumpririam as condições para interrupção legal da gestação; entretanto, a prática do aborto previsto em lei em hospitais públicos é exceção, provavelmente por desconhecimento dos médicos a respeito da legislação brasileira referente ao aborto. OBJETIVO: Avaliar o conhecimento e a opinião dos ginecologistas e obstetras filiados à Federação Brasileira das Associações de Ginecologia e Obstetrícia (FEBRASGO) sobre a legislação brasileira referente ao aborto, e sua correlação com algumas características sociodemográficas dos entrevistados. MÉTODOS: Foram enviados 14.320 questionários para serem respondidos por todos os membros da FEBRASGO, com taxa de resposta de 30,2% (4.323 questionários). RESULTADOS: A maioria apresentou uma boa compreensão das situações previstas na legislação e baixo conhecimento a respeito dos documentos necessários para a realização do aborto, exceto nos casos de malformação congênita grave, apresentando associação com a idade, tempo de prática e número de filhos. DISCUSSÃO E CONCLUSÕES: A pouca informação sobre os requerimentos legais para realizar um aborto permitido pela lei pode ser um dos principais fatores responsáveis pela falta de acesso ao aborto legal no Brasil.